Competencies of hospital managers – A systematic scoping review - Ndayishimiye, Costase; Dubas-Jakóbczyk, Katarzyna; Holubenko, Anastasia; Domagała, Alicja (Frontiers in Public Health, 2023)
Hospital managers around the world work under constant pressure to adapt their organizations to new challenges and health policy goals. This requires a comprehensive set of competencies. The objective of this scoping review was to identify, map, and systematize the literature on hospital manager competencies. The review involved six steps: 1) defining research questions; 2) identifying relevant literature; 3) selecting publications; 4) data extraction; 5) data analysis and result reporting; and 6) consultations. A total of 57 full-text publications were included (46 empirical studies, six literature reviews, four expert opinions/guidelines, and one dissertation). Interest in this topic has grown in recent years, with most of the identified studies published since 2015. The empirical studies fall into three major groups: 34.8% (16/46) examined hospital managers’ competencies in terms of their types or classifications; 30.4% (14/46) focused on their measurement; and 30.4% (14/46) examined both aspects. In majority of studies, both ‘hard competencies,’ such as specific technical knowledge or skills acquired through practical training, and 'soft competencies,' e.g., adaptability, leadership, communication, teamwork, are echoed for effective hospital management. These point out the importance of both ‘external’ formal education trainings as well as ‘internal’ peer-support and/or coaching as complementary competency improvement approaches. This scoping review helps build a knowledge base around the topic and provides implications for future research. The latter can involve: a targeted systematic review addressing the methods for measuring the level of competence of hospital managers or studies focused on identifying the need for new types of competencies.